Processing of degradable ulvan 3D porous structures for biomedical applications - Alves, A. (2013)
The interest in ulvan within a biomedical framework increases as the knowledge of this polysaccharide evolves. Ulvan has been recently proposed as a potential biomaterial, and structures based on this polysaccharide are now being studied for different biomedical applications. In this work, a novel porous structure based on cross-linked ulvan was designed and characterized. Its mechanical performance, water-uptake ability and weight loss were assessed, morphology analyzed through scanning electron microscopy, and morphometric parameters quantified by microcomputed tomography. Cell viability and cell proliferation were evaluated in order to estimate the cytotoxicity of these structures and respective degradation products. Produced ulvan structures revealed remarkable ability to uptake water (up to ∼ 2000% of its initial dry weight) and are characterized by a highly porous and interconnected structure. Furthermore, these ulvan structures underwent nontoxic degradation, and cells remained viable through the time of culture. These results position ulvan structures as prospective blocks that can be further functionalized in order to acquire the desired stability and needed biological interactivity to be used as tissue-engineered structures.